HALAL COSMETICS INDUSTRY FOR SUSTAINABLE DEVELOPMENT: A SYSTEMATIC LITERATURE REVIEW - Adlin Masood; Sri Rahayu Hijrah Hati; Alina Abdul Rahim (International Journal of Business and Society, 2023)
In 2019, Muslim expenditure on halal cosmetics reached USD66 billion globally and projected to attain USD75 billion in 2024 (GIER 2020/21) thus representing a substantial and sustainable opportunity for nations seeking economic security. Many halal cosmetics SMEs have venture into this emerging sector, but not all were successful. Halal cosmetics sector is still in its infancy thereby few literature reviews have been conducted worldwide to evaluate research gaps in the halal cosmetics and skincare business domain. The present study integrated multiple methods analysis and the publication standard ROSES (RepOrting standards for Systematic Evidence Syntheses). This study used bibliographic databases namely Scopus, ScienceDirect, Google Scholar and Springer Link. Only 31 articles from 761, met the criteria and were studied, revealing five main themes that were subdivided into 19 sub-themes. The outcome of this systematic review process enables identification of existing knowledge breach in the field, serves as the basis for conducting future research on halal cosmetics and skin care in a systematic manner, and paves the way towards doing further research to assist policy makers and business sectors to close the apparent gap. This understanding will enable emerging nations to achieve sustainable development goals through halal cosmetics industry.